(untitled) (International Journal of Physiotherapy, 2025)
Background: Among women, pelvic floor dysfunction (PFD) is a significant health issue, especially in rural environments where access to healthcare is restricted. Using the Pelvic Floor Distress Inventory-20 (PFDI-20), this extensive survey evaluated the frequency and insights into pelvic floor dysfunction among rural Jaipur, India, residents. Methods: A cross-sectional study was conducted among women residing in rural areas of Jaipur. It involved 94 women, who gave important information on the degree and features of PFD in this population. The study aimed to assess the prevalence and impact of pelvic floor dysfunction using the validated Pelvic floor dysfunction inventory (PFDI-20) Questionnaire. Results: Ninety-four women participated in the survey. The mean total PFDI-20 score was 23.5 ± 37.39, with subscale scores of 9.35 ± 16.09 (UDI-6), 5.32 ± 12.06 (CRAD-8), and 8.82 ± 15.11 (POPDI-6). Symptom severity analysis showed that 51% had no symptoms, 19% mild, 19% moderate, and 10% severe. Strong correlations were found between total and subscale scores (POPDI-6: r = 0.90, CRAD-8: r = 0.82, UDI-6: r = 0.86; p < 0.001). Urinary symptoms contributed most to the overall burden. No significant correlation was found between age and PFDI-20 scores (p > 0.005). Conclusion: This study emphasizes how urgently better healthcare access and PFD awareness are needed in rural Indian communities. The information gathered will form the basis for creating focused treatments and instructional campaigns aimed at pelvic floor dysfunction in underprivileged groups, improving health outcomes and quality of life for impacted women.